Site- and Time-Dependent Compositional Shifts in Oral Microbiota Communities - Esberg, Anders; Eriksson, Linda; Johansson, Ingegerd (Frontiers in Oral Health, 2022)
Objectives: The oral microbiota plays a significant role in oral health. The present study aims to characterize variations in oral microbiota relative to collection site, dynamics of biofilm accumulation and inherent inter-individual differences. Methods: Whole stimulated saliva and tooth biofilm samples from 16 defined tooth regions were collected after 1, 2, or 3 days without oral hygiene (accumulation time) in six healthy adults with no signs of active caries or periodontal disease. The routines and conditions before and between sample collections were carefully standardized. Genomic DNA was extracted, and the V3-V4 regions of the 16S rRNA gene was amplified by PCR and sequenced on an Illumina MiSeq platform. Sequences were quality controlled, ASVs clustered, and taxonomic allocation performed against the Expanded Human Oral Microbiome Database. Microbial community profiles were analyzed by multivariate modeling and a linear discriminant analysis effect size method. Results: The overall species profile in saliva and tooth biofilm differed between participants, as well as sample type, with significantly higher diversity in tooth biofilm samples than saliva. On average, 45% of detected species were shared between the two sample types. The microbiota profile changed from the most anterior to the most posterior tooth regions regardless of whether sampling was done after 1, 2, or 3 days without oral hygiene. Increasing accumulation time led to higher numbers of detected species in both the saliva and region-specific tooth biofilm niches. Conclusion: The present study confirms that the differences between individuals dominate over sample type and the time abstaining from oral hygiene for oral microbiota shaping. Therefore, a standardized accumulation time may be less important for some research questions aiming at separating individuals. Furthermore, the amount of DNA is sufficient if at least two teeth are sampled for microbiota characterization, which allows site-specific characterization of, for example, caries or periodontitis.